2019
DOI: 10.1002/nafm.10275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fishery‐Related Fight Time and Air Exposure on Prespawn Survival and Reproductive Success of Adult Hatchery Steelhead

Abstract: In recent years, increased scrutiny has been placed on the physiological effects of exhaustive exercise and air exposure on caught‐and‐released fish. Steelhead Oncorhynchus mykiss broodstock in the South Fork Clearwater River, Idaho, were collected by anglers during a winter fishery (water temperatures of 2–5°C); this enabled fight and air exposure times to be recorded to determine their influence on prespawn survival and progeny survival to the fry stage in the hatchery. The average fight time during angling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Additional fishing regulations could be implemented in an attempt to limit catch‐and‐release mortality and generally include gear and fish handling restrictions. However, findings in the literature on the effectiveness of these regulations at meeting targets for catch‐and‐release mortality are mixed and are likely context specific (Nelson et al 2005; Chiaramonte et al 2018; Twardek et al 2018; Whitney et al 2019). Although such regulations may be effective in certain circumstances, they are likely an imprecise tool to meet management objectives compared to the other management strategies evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additional fishing regulations could be implemented in an attempt to limit catch‐and‐release mortality and generally include gear and fish handling restrictions. However, findings in the literature on the effectiveness of these regulations at meeting targets for catch‐and‐release mortality are mixed and are likely context specific (Nelson et al 2005; Chiaramonte et al 2018; Twardek et al 2018; Whitney et al 2019). Although such regulations may be effective in certain circumstances, they are likely an imprecise tool to meet management objectives compared to the other management strategies evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of anadromous salmonids and C&R have been performed on fish during their spawning migrations into freshwater, with angling events occurring before reproduction (Havn et al ., 2015; Lennox et al ., 2015; Robinson et al ., 2015; Thorstad et al ., 2007; Twardek et al ., 2019; Whitney et al ., 2019). However, to our knowledge, the impact of angling events on post‐spawn fish has not been studied extensively in S. trutta or other salmonids.…”
Section: Discussionmentioning
confidence: 99%
“…In its ESA section 4(d) rules for steelhead, NMFS noted that research conducted on catch-andrelease mortality of steelhead in the northwestern United States and British Columbia showed an average mortality rate below 5% (National Marine Fisheries Service 2019). A recent study that used angler-caught steelhead for hatchery broodstock found that angling-related mortality was 3% in the Clearwater River (Whitney et al 2019). As such, IDFG uses a conservative 5% catch-and-release mortality rate for wild steelhead in the management of steelhead fisheries (Marshall 2001; Idaho Department of Fish and Game 2010).…”
Section: Impact Statementmentioning
confidence: 99%
“…Several studies have assessed the influence of angling on steelhead survival and have found relatively low mortality rates. Whitney et al (2019) evaluated the role of angling-specifically fight time and air exposure-on survival and reproduction of steelhead. Study fish were from an ongoing angler-caught hatchery broodstock program on the South Fork Clearwater River, Idaho.…”
Section: Fatementioning
confidence: 99%
See 1 more Smart Citation